INVITRO AND INSILICO ANALYSIS OF POTENTIAL ANTIOXIDANT FROM BERBERIS ARISTATA AND ITS SUBSTITUTES - J. KUMAR,; S.TAMILSELVI,; K. P. KANNAN, (International Journal of Pharma and Bio Sciences, 2014)
Antioxidative properties of extracts from plants have become a great interest due to their possible uses as natural additives to replace synthetic ones. The antioxidant potential of the plant extracts resulted by DPPH, ABTS and FRAP assays indicated that the extracts not only possess antioxidant activity but also the free radical scavenger capability. The utility and choice of in silico screening tools are dependent on the reason for their use and/or the nature of the output generated. The interaction profile of PKC alpha protein and Berberin complex indicates that the Berberin interacts at Phenylvaline and valine residue of protein showing that the Berberine has hydrophobic, non polar interaction whereas non covalent interaction via hydrogen bonding at the mentioned active site residues of protein. The results were further performed regarding the protein-ligand complex stability by performing a Molecular Dynamics simulation run of the complex for 100 ps using MacroModel module of Schrodinge suite. The simulation run showed that the complex is stable with time evolution. The in silico study of protein-Berberine complex rendered clear picture of effective interaction of Berberine with the protein.